Analysis of sustainable biological aspects of Scottish seine net in the waters of Majene, Indonesia. Issue 1 (October 2021) - Najamuddin,; Palo, Mahfud; Assir, Andi; Hardianti,
Abstract: Ministry of Marine Affair and Fisheries decree No.2 of 2015 states that the Scottish seine net is one of the fishing gears that is prohibited because the size of the fish catches were not suitable for catching. The purpose of this study was to evaluate the Scottish seine net fishing gear on the technical and biological aspects. The method used in this research is the survey method on the Scottish seine net and direct measurement of fork length and body circumference at dorsal fin base. The analysis used in this study is a description equipped with a graph, gonad maturity levels were analysis morphologically, determination of the first gonad maturity size using the Udupa method. The shortfin scads fish is the dominant fish caught in the Majene waters. The results showed that most of the scads caught by the Scottish seine net were fit for catching. The size of the fish that is suitable for catching depends on the position of the fishing area. The further away the fishing area is from the coastline, the larger portion of fish suitable for catching. The first gonads mature of shortfin scads fish in Majene waters in the fork length range of 205 – 208 mm for males and 211 – 216 mm for females. In order to catch shortfin scads fish that is suitable for catching, the minimum mesh size is 59.5 m for gill nets, and 39.7 mm for fishing gear that does not entangle.